Hepcidin Downregulation Correlates With Disease Aggressiveness And Immune Infiltration in Liver Cancers - Wang, Jinhu; Liu, Wang; Li, Jean C.; Li, Mingyi; Li, Benyi; Zhu, Runzhi (Frontiers in Oncology, 2021)
Background: Hepcidin is a polypeptide hormone mainly produced by hepatocytes to modulate systemic iron balance. A drastic downregulation of the hepcidin gene was found in liver cancers. However, there is a paucity of information about the clinical significance of hepcidin gene downregulation in liver cancers. Methods: Hepcidin expression profiles were assessed using multiple public datasets via several bioinformatics platforms. Clinical and pathological information was utilized to stratify patients for comparison. Patient survival outcomes were evaluated using the Kaplan-Meier plotter, a meta-analysis tool. Tumor immune infiltration was analyzed using the single sample gene set enrichment analysis (ssGSEA) approach on the TCGA dataset. Hepcidin antagonist Fursultiamine was used to treat liver cancer HepG2 and Huh7 cell lines together with Sorafenib. Results: Hepcidin gene was predominantly expressed in benign liver tissues but drastically decreased in liver cancer tissues. Hepcidin reduction in liver cancers correlated with risk factors like non-alcoholic fatty liver disease (NAFLD) and liver fibrosis, as well as cancer grade and tumor stage. Hepcidin downregulation was associated with a rapid cancer progression and worse disease-specific survival, especially in patients of the White race without alcohol consumption history. Hepcidin expression in liver cancer tissues positively correlated with BMP6/IL6 cytokines and cytotoxic immune infiltration. Blocking hepcidin action with its antagonist Fursultiamine moderately reduced Sorafenib-induced apoptotic cell death in HepG2 and Huh7 cells. Conclusion: Hepcidin downregulation in liver cancers correlated with liver cancer risk factors, cancer aggressiveness, cytotoxic immune cell infiltration, and patient survival outcomes. BMP6/IL6 pathway insufficiency is a potential cause of hepcidin downregulation in liver cancers.